Anatomic Features and Clinical Outcomes of 48 Distal Anterior Cerebral Artery Aneurysms. Issue 3 (August 2016) - Yi, Hojun; Hwang, Hyung Sik; Choi, Ji Won; Shin, Il Young; Choi, Il
Abstract : Objective: This study presents 48 patients, with special attention given to the clinical and radiologic characteristics, as well as the outcomes of surgical and endovascular treatment. Materials and Methods: A total of 1941 patients with cerebral aneurysms were treated from January 2003 to June 2011. Data reviewed included the patient's age, sex, Hunt-Hess grade, characteristics of the imaging study, procedure-related complications, and clinical outcomes. Aneurysm locations were divided into 3 groups [group I: pericallosal-callosomarginal (PerA-CMA) superior (above the genu of corpus callosum) type; group II: pericallosal-callosomarginal (PerA-CMA) inferior (below the genu of corpus callosum) type; group III: pericallosal-frontobasal (PerA-FPA) type]. Results: A total of 48 patients with distal anterior cerebral artery aneurysms were included in the study. Conventional or computed tomography-angiography revealed that group I 18 (37.5%), group II 24 (50%), and group III 6 (12.5%), respectively. Fifteen (31.3%) patients underwent endovascular coiling and 33 (68.7%) patients underwent microsurgical treatment. Initial mean Glasgow Coma Scale of group of coil embolization was 14.0 and group of microsurgical treatment was 11.2 and the Glasgow Outcome Scale score after coiled patients was 4.6 and 3.7 after clipping. Conclusions: There are no statistical significant difference of clinical outcomes in 3 different anatomic locations, but 6 mortalities with initial poor grade were treated by clipping and were caused by severe cerebral vasospasm, sepsis, and pneumonia( P =0.0388). Therefore, if initial Glasgow Coma Scale was good and the dome to neck ratio of aneurysm was >2.0, endovascular coil embolization may be the best option of treatment of distal anterior cerebral artery aneurysms.